Inovasi Pelayanan Konsultasi dan Pengaduan Administrasi Kependudukan Secara Terpadu (D’Trust) di Dinas Kependudukan dan Catatan Sipil Kota Pinrang - Juwita; Andi Nurul Afana Fitra; Mita Arnika (PENA BANGSA: Bisnis dan Tata Kelola Publik Adaptif, 2025)
Public demand for excellent service forces the government to make various innovations. Innovation is one of the solutions in realizing good government services such as those carried out by the Population and Civil Registration Office of Pinrang City which created an integrated population administration consultation and complaint service innovation (D'Trust) designed to overcome problems in resolving complaints and lack of access to information. The research method used is descriptive qualitative research. The theory used in this research is the theory of innovation attributes proposed by Everett M. Rogers in Suwarno (2008) which consists of 5 (five) indicators, namely relative advantage, compatibility, complexity, triability, and observability. Data collection techniques such as interviews, documentation and observation. The results of the study prove that the D'Trust innovation launched by the Population and Civil Registration Office of Pinrang City has run well and optimally because it can facilitate the work of employees in managing community complaints in a systemized and integrated manner. In terms of benefits and service processes, it becomes more effective and efficient because public complaints can be made directly and online which are received by officers who then input, classify, analyze and provide solutions to these complaints according to the intended administrative services. The D'Trust platform is user-friendly enough to be operated by officers although initially it requires adaptation to the new technology.